EVALUATION OF HOTEL TAX POTENTIAL AND ITS CONTRIBUTION TOWARDS LOCAL REVENUE (A Case Study On Financial Management Department Of Tangerang City) - Iman Taufik (Jurnal Ilmiah Mahasiswa FEB, 2015)
The aim of this study is to determine the potential of hotel tax and hotel tax contribution to regional revenue which is owned by the City of Tangerang. The method used is quantitative descriptive, namely research by collecting data in the form of figures and calculate and explain the data. The data collection techniques is done by documentation and study of literature.       The results showed that the contribution of hotel tax to PAD Tangerang City is still very small, but it has great potential. Taxes contribution to revenue in 2011-2014 was always declining. In 2011, the contribution amounted to 4.01%, 2012 amounted to 3.38%, 2013 amounted to 3.27% and in 2014 amounted to 2.57%. Meanwhile, the comparison between the realization of the potential of hotel tax revenues in 2011-2014 was always increasing. In 2011 amounted to 6.35%, 2012 amounted to 5,33%, 2013 amountd to 8,26% and 2014 amounted to 46.77%. It can be concluded that the realization of hotel tax revenues in Tangerang does not reflect the real potential. Therefore, the Office of Financial Management should further optimize Tangerang City hotel tax revenues in order to increase local revenue. Keywords: Hotel Tax Contribution, Hotel Tax Potential, Regional Revenue,                 Tangerang City.